Game Edukasi Pengenalan Binatang Pada Anak Usia Dini 4-6 Tahun Menggunakan Metode Finite State Machine - Saputro, Vito Rizki Haryo; Wahyuddin, Moh. Iwan (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Currently, games are in great demand by various age groups, especially children. Game is one of the alternative media that is very effective in creating educational situations for children to play. Interactive games can trigger children's interest in playing and can help children be more active in the reactions given by the system. This educational game aimed at early childhood aims to add insight and knowledge to children, as well as train children's motor skills in playing, train memory, hone children's creativity, as well as a fun entertainment medium. In this study, the design of an animal recognition game was built using the Adobe Flash CS6 application and with the Finite State Machine or FSM as the method used to design a control system by implementing three standard system work matters, namely states, events and actions. actions). This game uses the Finite State Machine or FSM technique with the aim that this application is easier for children aged 4-6 years to use. Development of an animal introduction educational game application in the form of an .exe file that can run on a laptop or computer device. The results of tests carried out using the System Usability Scale method obtained a score of 70.8%, the results were categorized as acceptable and ready for use.